PENGARUH TANGGUNG JAWAB SOSIAL KORPORAT KEPADA PEKERJA TERHADAP KINERJA EKONOMI PERUSAHAAN MANUFAKTUR DI BURSA SAHAM INDONESIA - Dina Madinah; Mara Ridhuan Che Abdul Rahman; Shifa Mohd Nor; Mohd Rizal Palil (Jurnal Riset Akuntansi Terpadu, 2019)
Worker's Corporate Social Responsibility (CSR - P) is the responsibility and obligation of the company's management. Workers are important stakeholders because they are involved in the company's operational activities in an effort to achieve company goals. This study will examine the effect of CSR - P, size and leverage on the company's economic performance which expressed by return on assets (ROA) and worker productivity. This research will be carried out on manufacturing companies on the main board of the Indonesian Stock Exchange for period year 2015, 2016 and 2017. After the regression analysis has been carried out, the study finds that CSR - P has a positive significant effect on ROA and worker productivity. The results of this study indicate that the implementation of CSR - P by companies is not only to fulfil the rights of workers and to carry out company obligations but is found to have an influence to increase ROA and company productivity. In addition, for manufacturing companies with a high level of risk of health and safety problems the implementation of CSR - P can be used as a solution to overcome the possibility of problems with workers due to the company's operational activities. While size and leverage are found to have a significant influence but negative on ROA and productivity. This means that size and leverage are not factors that can affect ROA and worker productivity. This study tries to provide input to the company to pay more attention and maximize the implementation of CSRP which is found to be able to influence the ROA stage and worker productivity.